Semantic technologies for business and information systems engineering concepts and applications - Smolnik, Stefan; Teuteberg, Frank 1970-; Thomas, Oliver 1971- (Premier reference source, 2012)
"This book investigates the application of semantic technologies to business and information systems engineering. This reference work assists the reader in gaining knowledge on applying semantic technologies for advanced business information systems, in annotating semantics to business processes, and in semantically integrating advanced business information systems." - Provided by publisher